Immunotherapy and targeted therapy for lung cancer: Current status and future perspectives - Zulfiqar, Bilal; Farooq, Asim; Kanwal, Shahzina; Asghar, Kashif (Frontiers in Pharmacology, 2022)
Lung cancer has the highest incidence of morbidity and mortality throughout the globe. A large number of patients are diagnosed with lung cancer at the later stages of the disease. This eliminates surgery as an option and places complete dependence on radiotherapy or chemotherapy, and/or a combination of both, to halt disease progression by targeting the tumor cells. Unfortunately, these therapies have rarely proved to be effective and this necessitates the search of alternative preventive approaches to reduce the mortality rate of lung cancer. One of the effective therapies against lung cancer is comprised of targeting tumor microenvironment. Like any other cancer cell, lung cancer cells tend to use multiple pathways to maintain their survival and suppress different immune responses from the host’s body. This review comprehensively covers the role and the mechanisms that involve Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB) in lung adenocarcinoma and methods of treating it by altering the tumor microenvironment. It focuses on the insight and understanding of the lung cancer tumor microenvironment; chemokines, cytokines and activating molecules that take part in angiogenesis and metastasis. The review paper accounts for the novel and current immunotherapies available for lung cancer in clinical trials and in the research phases in depth. Special attention is paid to marking out single or multiple genes that are required for malignancy and survival while developing targeted therapies for lung cancer treatment.